Comparative Effectiveness of Varenicline and Nicotine Replacement Therapy for Smoking Cessation in Older and Younger Smokers: A Prospective Cohort in Taiwan. Issue 2 (22nd December 2017) - Chang, Po-Yin; Shiu, Ming-Neng; Yuan, Yu-Ting; Chang, Hui-Chin; Su, Pei-Yu; Lan, Tsuo-Hung
Abstract: Introduction: The effectiveness of varenicline compared with nicotine replacement therapy (NRT) in achieving smoking cessation in older smokers has not been investigated. This study prospectively compared the effectiveness of varenicline relative to NRT in smokers aged 25–54 years and separately in smokers aged 55 years or older. Methods: Among 13 397 smokers participating in the Smoking Cessation Program in Taiwan, 2012–2015, 6336 (19.2%, aged ≥55) received varenicline and 7061 received NRT patch or gum (23.2%, aged ≥55). Participants self-reported smoking behaviors by phone interview after 6 months. Logistic regression models estimated odds ratios (ORs) and 95% confidence intervals (CIs) for 7-day, 1-month, and 6-month point-prevalence abstinence. Age-specific models adjusted for sex, education, marital status, smoke-years, nicotine dependence, medical institution, clinic visit number, and duration of medication received. Results: Among smokers aged 25–54 years, varenicline users had a greater point-prevalence abstinence than NRT users (e.g., 7-day point-prevalence: 34.0% vs. 23.5%), with adjusted OR ranging from 1.23 (CI: 1.09–1.39; 6-month point-prevalence) to 1.37 (CI: 1.24–1.50; 1-month point-prevalence). Among smokers aged 55 years or older, point-prevalence was similar for varenicline and NRT users (e.g., 7-day point-prevalence: 32.3% vs. 33.1%), and ORs did not suggest that varenicline has greater effectiveness than NRT. Sex and level of nicotine dependence did not modify the age-specific effectiveness of varenicline relative to NRT. Conclusions: Varenicline did not offer greater effectiveness in achieving abstinence than NRT for smokers 55 years or older, whereas it was more effective than NRT in smokers aged 25–54 years. These findings highlighted the need for age-specific approaches for effective tobacco control. Implications: In this prospective investigation of a national cohort, older smokers (aged ≥55 years) who received varenicline did not have a greater point-prevalence abstinence after 6 months compared with those who used NRT patch or gum. Younger smokers (aged 25–54 years) who received varenicline had a greater likelihood of abstinence than NRT users. Sex and nicotine dependence did not modify the age-specific effectiveness of varenicline relative to NRT patch or gum. Age-appropriate approaches for effective tobacco control are needed.